Acute Ketamine Facilitates Fear Memory Extinction in a Rat Model of PTSD Along With Restoring Glutamatergic Alterations and Dendritic Atrophy in the Prefrontal Cortex - Sala, Nathalie; Paoli, Caterina; Bonifacino, Tiziana; Mingardi, Jessica; Schiavon, Emanuele; La Via, Luca; Milanese, Marco; Tornese, Paolo; Datusalia, Ashok K.; Rosa, Jessica; Facchinetti, Roberta; Frumento, Giulia; et al. (Frontiers in Pharmacology, 2022)
Stress represents a major risk factor for psychiatric disorders, including Post-Traumatic Stress Disorder (PTSD). Recently we dissected the destabilizing effects of acute stress on the excitatory glutamate system in the prefrontal cortex (PFC). Here we assessed the effects of single subanesthetic administration of ketamine (10 mg/kg) on glutamate transmission and dendritic arborization in the PFC of footshock (FS) stressed rats, along with changes in depressive, anxious and fear extinction behaviors. We found that ketamine, while inducing a mild increase of glutamate release in the PFC of naïve rats, blocked the acute stress-induced enhancement of glutamate release when administered 24 or 72 h before, or 6 h after FS. Accordingly, the treatment with ketamine 6 h after FS also reduced the stress-dependent increase of spontaneous excitatory postsynaptic currents (sEPSCs) amplitude in prelimbic (PL)-PFC. At the same time, ketamine injection 6 h after FS was found to rescue apical dendritic retraction of pyramidal neurons induced by acute stress in PL-PFC and facilitated contextual fear extinction. These results show rapid effects of ketamine in animals subjected to acute FS, in line with previous studies suggesting a therapeutic action of the drug in PTSD models. Our data are consistent with a mechanism of ketamine involving re-establishment of synaptic homeostasis, through restoration of glutamate release, and structural remodeling of dendrites.